Creencias en salud y prácticas de prevención de los contactos de pacientes con tuberculosis pulmonar. Chepén 2011 - Mendoza Huacacolque, Mariella Lisseth (2011)
This study is a descriptive, cross – sectional was conducted in order to determine the relationship between Health Beliefs and Practices for the Prevention of contacts of patients with Pulmonary Tuberculosis Control Program for Tuberculosis Hospital Chepen support during the month of July 2011, the sample universe was composed of 50 contacts for data collection using two instruments, one that enabled it to assess the Health Belief and the other assessed the Prevention Practices of contacts. Data were tabulated and presented in simple tables and double entry and processed by the Independency Standards Test (Chi Square). It is concluded that 86 per cent of contacts had positive Health Beliefs and 14 per cent negative, 84 per cent had adequate prevention practices and 16 per cent inappropiate. The Health Belief is a highly significant relationships (p=0.000 ) with prevention practices.